The influence of Blaž Kocen (Blasius Kozenn) and his geographical atlas on the development of Croatian school cartography - Slukan Altić, Mirela (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2021)
In this paper, we analyze the importance of Kocen’s atlases for the development of Croatian school cartography. Comparing German and Croatian editions in the period between 1887 and 1943, we follow the progress in map printing, cartographic techniques, language redactions of toponymy as well as the inclusion of thematic maps and the influence of political discourse (German centralism vs. Slavic nationalisms) on the geographical scope and content of maps used in the educational process.
Keywords: atlasi; Blaž Kocen; cartography; Croatia; geography of education; Hrvaška; kartografija; Kocen, Blaž; nacionalna identiteta; national identity; šolska geografija